2012
DOI: 10.1097/hjh.0b013e328356c257
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and vascular calcification

Abstract: It is now well established that hypertension is accompanied by remodeling of the arterial wall with significant modifications in extracellular matrix composition and in vascular cell phenotype. Some of these changes, particularly elastin fragments generation, increased proteases activity and activation of transforming growth factor-β signaling together with deposition of collagen and proteoglycans might generate a permissive soil for vascular calcification. On the other hand, calcium deposits within large arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 94 publications
0
51
0
1
Order By: Relevance
“…22, 24 Elastin degradation, as may occur from adverse central hemodynamics, leads to medial calcium deposition in animal models 25 and medial calcification may lead to further destruction of elastin. 13 While our CT technique, due to the lack of spatial resolution needed, cannot differentiate between intimal and medial coronary artery calcification, histopathology studies have shown that the overwhelming majority of calcification in subjects without known renal disease can be found in the intima of the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22, 24 Elastin degradation, as may occur from adverse central hemodynamics, leads to medial calcium deposition in animal models 25 and medial calcification may lead to further destruction of elastin. 13 While our CT technique, due to the lack of spatial resolution needed, cannot differentiate between intimal and medial coronary artery calcification, histopathology studies have shown that the overwhelming majority of calcification in subjects without known renal disease can be found in the intima of the coronary arteries.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, recent evidence suggests that vascular remodeling in the presence of increased stiffness may contribute to medial and intimal calcification. 22 …”
Section: Introductionmentioning
confidence: 99%
“…We have summarized these as follows: i) both elastin fragment generation and the deposition of collagen fibers have been linked to remodeling of the arterial wall in hypertension. These changes contribute to the reduction of the elasticity of the vessel associated with extracellular matrix composition and vascular cell phenotype variation (26). ii) The chronic form of heart failure and progressive cardiac dysfunction is constituted by myocardial remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension is an independent and strong predictor of vascular calcification4, which is accompanied with immune cell infiltration in the blood vessels, including monocytes/macrophages, lymphocytes, granulocytes56. Among these, monocytes/macrophages activation, including pro-inflammatory “classical” activation profile (M1) and anti-inflammatory “alternative” activation profile (M2), was involved in the hypertension-related vascular disease789.…”
mentioning
confidence: 99%